Directors’ duties in proximity of crisis in Italian and Spanish law in the framework of the Insolvency Directive - Serafini, Stefania (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The contribution examines the changes introduced in the Italian and Spanish legal sys- tems in implementation of the EU Insolvency Directive of 20 June 2019 N. 1023, and their impact on the directors’ duties regarding the management of the company in crisis. The analysis shows how the regulatory evolution has led to a convergence of the approaches provided for in the two legislative systems, which find the following points of contact: (i) the favour towards solutions that allow the restructuring of the company, rather than its cessation and liquidation, (ii) the attribution to the directors of a sphere of discretionary competence in the continuation of management of the company and in the identification of the solution that allows the crisis to be overcome as soon as possible. The contribution also highlights the important differences in the Insolvency law of the two countries, including: (i) the specification in the Italian legal system of the directors’ duties in the face of the crisis, which is absent in the Spanish legal system; (ii) the less flexibility of the Spanish discipline of preconcurso with respect to the crisis regulation tools provided by the Italian “Codice della Crisi di Impresa e dell’Insolvenza”.